Research progress on argon atomized nickel-based powder metallurgy superalloys and powder characteristics - ZHANG Qiang; ZHENG Liang; XU Wen-yong; LI Zhou; ZHANG Guo-qing; XIE Jian-xin (Fenmo yejin jishu)
The development of nickel-based powder metallurgy (PM) superalloy, the technical features of argon atomized (AA) powder manufacturing, the characteristics of AA nickel-based superalloy powders, and the development direction of nickel-based superalloy powders for additive manufacturing (AM) were summarized in this paper. Meanwhile, the powder morphology, particle size control, oxidation characteristics, degassing behavior, and formation and control of defects for the nickel-based superalloy powders were mainly emphasized. The internal relationship between the powder characteristics and alloy defects was discussed, the research progress of the defect elimination measures was analyzed, and the quality optimization future of nickel-based superalloy powders used for the turbine disk was clarified. Moreover, the application of high-quality AA nickel-based superalloy powders to promote the AM technology in the aerospace field was prospected.